Pacing characteristics of international sprint kayak athletes - Borges, T. O.; Bullock, N.; Coutts, A. J. (International Journal of Performance Analysis in Sport, 2013)
This study aimed to profile pacing strategies and pacing profile of world-class kayakers during world championships. Data were from publically available websites of eight international competitive seasons (2004 - 2011). Data represent percentage average race pace. Mixed ANOVA was used to compare pacing (250 m splits) and race level (A and B-finals) and crew boats. Effect size was calculated converting F-values into r-values (P < 0.05). There were significant interactions between splits and season (F7.99, 255.7=13.08, P <0.001, r=0.05), splits and boat crew (F5.33, 255.7=4.82, P <0.001, r=0.02), race level, the split speed and the competitive season (F8.49, 271.5=2.07, P =0.035, r=0.01) and the race level, the split speed and the boat crews (F5.66, 271.5=2.28, P =0.04, r=0.01) for the 1000 m. There was a significant interaction between race level, split speed and boat crew (F1, 80=4.35, P =0.004, r=0.05) in the 500 m. Performances of A and B-finals were significantly different. In conclusion, pacing of sprint kayakers can vary according to race level (A or B-finals, elite or sub-elite respectively), crew (K1, K2 and K4), split distances (250 m splits) and competitive seasons. Additionally, our data suggests there may exist specific crew boat dynamics and, therefore, specific race demands.